Effect of sugary substances on organic substrates degradation for compost elaboration - Álvarez-Sánchez, Ana Ruth; Llerena-Ramos, Luis Tarquino; Reyes-Pérez, Juan José (REVISTA TERRA LATINOAMERICANA, 2021)
Compost is the main degradation channel for organic waste, however, the whole process requires long maturation times, which is why the search for quick ways to decompose and transform these wastes into by-products with high agronomic value is essential. The objective of this study was to determine the effect of sugary substances on the degradation of organic substrates to elaborate compost. The substances investigated were sugar, molasse and cane juice (Saccharum officinarum), mixed with an organic substrate composed of 30% manure, 50% corn pancake, 10% legume remains, 9% soil and 1% ash. The experimental design was completely random, with 16 experimental units, one absolute control and four repetitions. The variables evaluated were the following: days for decomposition, temperature, humidity, substrate weight and nutriment content. Molasses mixed with organic waste decreased the decomposition period by 6 days (9.68%), relative to the control (62 days). The treatment added with molasses showed the greatest temperature decline (8.7 °C), although no significant differences were found between treatments, at the beginning and end of the trial. The moisture content among treatments ranged from 56.5 to 59.0%, however, differences were not significant. The molasses treatment showed the greatest weight loss (10.8 kg) during the organic substrate degradation; however, there were no differences in pH and nutrient content (B, Ca, Cu, K, Mg, N, P, S, Zn, and MO). The treatment with the highest concentration of nutrients was the conformed by organic substances and molasses, thus, its use or integration is recommended to accelerate the degradation process in compost.